2009
DOI: 10.3109/07380570903329628
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Cultural Competency, Clinical Reasoning, and Leadership Through International Outreach

Abstract: The Centennial Vision of the American Occupational Therapy Association (AOTA) has called for occupational therapy to be globally connected. Students can gain cultural competency, clinical reasoning, and leadership from attending didactic coursework and participating in discussions and clinical simulations. Immersing oneself in international settings, however, tends to have a greater impact on learning. The authors describe the outcomes of two international outreach programs: China Honors Immersion Program (CHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…Research has indicated that occupational therapy practitioners acknowledge the need to understand and develop cultural awareness and competency as a part of education and clinical practice (Cheung et al, 2002;Kale & Hong, 2007;Mu et al, 2010;Munoz, 2007;Murden et al, 2008;Rasmussen et al, 2005;Whiteford & St-Clair, 2002). Research shows that cultural awareness and competency are an evolving and developing process, yet continues to be "one of the least developed aspects of occupational therapy" (Awaad, 2003, p.358;Black & Wells, 2007).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has indicated that occupational therapy practitioners acknowledge the need to understand and develop cultural awareness and competency as a part of education and clinical practice (Cheung et al, 2002;Kale & Hong, 2007;Mu et al, 2010;Munoz, 2007;Murden et al, 2008;Rasmussen et al, 2005;Whiteford & St-Clair, 2002). Research shows that cultural awareness and competency are an evolving and developing process, yet continues to be "one of the least developed aspects of occupational therapy" (Awaad, 2003, p.358;Black & Wells, 2007).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
“…Occupational therapists must be aware and sensitive to cultural differences and must be able to consider cultural influences when selecting assessments and occupational interventions to meet the needs of their clients to improve quality of care and avoid any adverse impact (Cheung et al, 2002;Kale & Hong, 2007;Murden et al, 2008;Sood et al, 2014). The inclusion of the concept of culture and the development of cultural awareness in the occupational therapy curriculum is necessary to prepare students for globalization and respond to the demands of today's culturally diverse work settings (Kale & Hong, 2007;Mu et al, 2010).…”
Section: Cultural Competency and Occupational Therapy Educationmentioning
confidence: 99%
See 3 more Smart Citations